Ultimatum - Pineiro, R. J. (New York : Tor Book, 1994)
Navy lieutenant Kevin Dalton teams up with a beautiful Israeli spy and her band of Kurdish rebels to thwart Sadaam Hussein's revenge for the defeat in the Gulf War. Not an easy assignment because this time Iraq has the A-bomb. By the author of Siege of Lightning.
"A Tom Doherty Associates book."
Keywords: Persian Gulf War, 1991 -- Veterans -- Fiction; International relations -- Fiction; Intelligence service -- Fiction; Iraq -- Fiction; Novela estadounidense